Examining the Role of Life Review Therapy in Reducing Loneliness Among Older Adults - Qoyyimatus Zahro; Hyan Oktodia Basuki (Jurnal Keperawatan Profesional, 2026)
As people age, older adults become more vulnerable to physical and psychological issues that can reduce their ability to engage in social interactions, leading to loneliness, which negatively impacts their mental health and quality of life. One effective non-pharmacological intervention to address this problem is Life Review Therapy (LRT), a psychosocial therapy that encourages the elderly to reflect on their life experiences in order to accept the past positively and find deeper meaning in life. This study employed a pre-experimental design with a One Group Pre-Post Test approach involving 28 elderly participants selected through purposive sampling. The instruments used were the Life Review Therapy SOP and the UCLA Loneliness Scale Version 3, with data analyzed using the Wilcoxon signed rank test. The results showed a p-value of 0.000 (p < 0.05), indicating a significant effect of LRT in reducing loneliness among the elderly. Influencing factors included age, self-esteem, mental readiness, social support, and the condition of the nursing home environment. These findings affirm the effectiveness of LRT as a psychosocial intervention in gerontological nursing and suggest the need for further studies using a control group.